Pengaruh Brand Awareness dan Brand Ambassador terhadap Loyalitas Konsumen Melalui Kepuasan Konsumen Sebagai Variabel Intervening: Studi pada Konsumen Air Minum Crystalin di Kota Gresik - Syafira Chamila Rahma; Budi Prabowo (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
This research aims to determine and analyze the influence of Brand Awareness on Costumer Satisfaction, the influence of Brand Ambassadors on Costumer Satisfaction, the influence of Brand Awareness on Costumer Loyalty, the influence of Brand Ambassadors on Costumer Loyalty, the influence of Costumer Satisfaction on Costumer Loyalty, the influence of Brand Awareness on Costumer Loyalty through Costumers Satisfaction, the Influence of Brand Ambassadors on Costumer Loyalty through Costumer Satisfaction. The population of this research is Crystalin drinking water Costumers who live in Gresik. The sample used was 100 taken using purposive sampling technique. Data analysis in this research used SEM-PLS with SmartPLS software version 4.0. The research results show that Brand Awareness (X1) has a significant effect on Costumer Satisfaction (Z). Brand Ambassador (X2) has a significant effect on Costumer Satisfaction (Z). Brand Awareness (X1) has a significant effect on Costumer Loyalty (Y). Brand Ambassador (X2) has no significant effect on Costumer Loyalty (Y). Costumer Satisfaction (Z) has a significant effect on Costumer Loyalty (Y). Brand Awareness (X1) has a significant effect on Costumer loyalty (Y) through Costumer Satisfaction (Z). Brand Ambassador (X2) has a significant effect on Costumer Loyalty (Y) through Costumer Satisfaction (Z).